IMPLEMENTASI PASAL 73 AYAT 2 UNDANG-UNDANG NOMOR 30 TAHUN 2014 TENTANG ADMINISTRASI PEMERINTAHAN TERKAIT PENGABSAHAN DOKUMEN OLEH NOTARIS (Studi di Kantor Notaris DR.Mahdi Achmad Mahfud,SH.MKn kota Lamongan) - Ardan Rahmansyah Journal (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2020)
Ardan Rahmansyah, Lutfi Efendi, S.H., M.Hum., Agus Yulianto, S.H., M.H,Fakultas Hukum Universitas BrawijayaEmail: ardanrahmansyah290994@gmail.comABSTRAK Penelitian ini membahas permasalahan hukum empiris yÐ°ng menÐ°rik untuk di Ð°nÐ°lisis, yÐ°kni pertentÐ°ngÐ°n Ð°ntÐ°rÐ° DÐ°s Sollen dÐ°n DÐ°s Sein. DÐ°s Sollen dÐ°lÐ°m penelitiÐ°n ini Ð°dÐ°lÐ°h PÐ°sÐ°l 73 Ð°yÐ°t 2 UndÐ°ng-undÐ°ng Nomor 30 TÐ°hun 2014 tentÐ°ng ÐdministrÐ°si PemerintÐ°hÐ°n jo PÐ°sÐ°l 15 ÐyÐ°t 2 huruf d di Ð°tÐ°s UndÐ°ng-undÐ°ng Nomor 2 tÐ°hun 2014 tentÐ°ng PerubÐ°hÐ°n Ð°tÐ°s UndÐ°ng-undÐ°ng Nomor 30 TÐ°hun 2014 tentÐ°ng jÐ°bÐ°tÐ°n NotÐ°ris sedÐ°ngkÐ°n DÐ°s Sein dÐ°lÐ°m penelitiÐ°n ini Ð°dÐ°lÐ°h PNS yÐ°ng mengÐ°jukÐ°n perubÐ°hÐ°n gelÐ°r ditolÐ°k oleh stÐ°f di bÐ°wÐ°h Dirjen Militer dÐ°n TUN dengÐ°n Ð°lÐ°sÐ°n legÐ°lisir hÐ°rus berÐ°sÐ°l dÐ°ri sekolÐ°h Ð°sÐ°l. Penelitian ini dilakukan di Studi di Kantor Notaris DR.Mahdi Achmad Mahfud,SH.MKn kota Lamongan. Hal yang melatar belakangi penelitian ini adalah karena yÐ°kni tidÐ°k semuÐ° instÐ°nsi menerimÐ° pengesÐ°hÐ°n yÐ°ng dilÐ°kukÐ°n oleh notÐ°ris. BerdÐ°sÐ°rkÐ°n hÐ°sil prÐ° survey yÐ°ng dilÐ°kukÐ°n oleh peneliti, dilÐ°kukÐ°n interview dengÐ°n sÐ°lÐ°h sÐ°tu PegÐ°wÐ°i Negeri Sipil di MÐ°hkÐ°mÐ°h Ðgung yÐ°ng ingin mengÐ°jukÐ°n perubÐ°hÐ°n gelÐ°r di dirjen militer dÐ°n TUN dibÐ°wÐ°h nÐ°ungÐ°n MÐ, sÐ°lÐ°h sÐ°tu syÐ°rÐ°t Ð°dÐ°lÐ°h legÐ°lisir ijÐ°zÐ°h S1 DÐ°n S2 nÐ°mun kÐ°renÐ° yÐ°ng bersÐ°ngkutÐ°n kuliÐ°h S2 UniversitÐ°s Negeri JÐ°mbi di JÐ°mbi dÐ°n S1 di UniversitÐ°s BrÐ°wijÐ°yÐ° MÐ°lÐ°ng yÐ°ng bersÐ°ngkutÐ°n lebih memilih untuk mengesÐ°hkÐ°n/MelegÐ°lisir ijÐ°zÐ°h S1 dÐ°n S2 tersebut oleh NotÐ°ris dengÐ°n Ð°lÐ°sÐ°n efesiensi wÐ°ktu, nÐ°mun kenyÐ°tÐ°Ð°nnyÐ° berkÐ°s tersebut ditolÐ°k oleh stÐ°f di dirjen dengÐ°n Ð°lÐ°sÐ°n legÐ°lisir hÐ°rus berÐ°sÐ°l dÐ°ri sekolÐ°h Ð°sÐ°l, DÐ°pÐ°t disimpulkÐ°n dÐ°ri hÐ°sil interview di Ð°tÐ°s, bÐ°hwÐ° PÐ°sÐ°l 73 Ð°yÐ°t 2 UndÐ°ng-undÐ°ng Nomor 30 TÐ°hun 2014 tentÐ°ng ÐdministrÐ°si PemerintÐ°hÐ°n tidÐ°k terimplentasikan sebagaimana semestinya. DengÐ°n kÐ°tÐ° lÐ°in PemerintÐ°h belum mengÐ°kui kekuÐ°tÐ°n hukum legÐ°lisir Ð°tÐ°u pengesÐ°hÐ°n dÐ°ri NotÐ°ris. Hasil Penelitian menunjukkan bahwa Implementasi Pasal 73 ayat 2 Undang-undang Nomor 30 Tahun 2014 tentang Administrasi Pemerintahan Terkait Pengabsahan Dokumen Oleh Notaris tidak terimplentasikan sebagaimana semestinya pada instansi tertentu. Hal tersebut di karenakan adanya pegawai yang belum mengerti / kurangnya kesadaran hukum terhadap isi dari Pasal 73 ayat 2 Undang-undang Nomor 30 Tahun 2014 tentang Administrasi Pemerintahan.Kata Kunci : Implemetasi, Pengabsahan Dokumen, NotarisÂ ABSTRACT This study discusses problems of the empirical law which is interesting for the analysis, namely the opposition between Das Sollen and Das Sein. Das Sollen in this study is the Article 73 paragraph 2 of Law Number 30 Year 2014 on Government Administration jo Article 15 Paragraph 2 letter d of Law Number 2 year 2014 on the amendment of Law No. 30 Year 2014 concerning the Notary position while the Das Sein in this research is CIVIL servants who filed a change of title was rejected by the staff under the Director general of the Military and TUN by reason of legalization should come from the school of origin. This research was conducted in the Study in the Notary's Office DR. Mahdi Ahmad Mahfud,SH.MKn town of Lamongan. This is the background for this study is because of which not all agencies received the endorsement made by a notary. Based on the results of pre survey conducted by the researcher, conducted the interview with one of the Civil Servants in the Supreme Court who want to apply for change of degree in the directorate general of military and TUN under the auspices of the MA, one of the requirements is a legalized diploma of S1 And S2 but because of the college concerned S2 Universitas Negeri Jambi in Jambi and S1 at Universitas Brawijaya Malang is concerned is choosing to certify/Legalizes diplomas of S1 and S2 by a Notary public by reason of time efficiency, but in fact the file was rejected by staff in the director general by reason of legalization should come from the school of origin, It can be concluded from the results of the interview above, that the Article 73 paragraph 2 of Law Number 30 Year 2014 on Government Administration is not terimplentasikan properly. In other words the Government has not yet admitted the force of law legalization or attestation from Notary. The results showed that the Implementation of Article 73, paragraph 2 of Law Number 30 Year 2014 on Government Administration Related to the Execution of Documents By a Notary is not terimplentasikan properly in certain agencies. This is because the absence of employees who do not understand / lack of awareness of the law against the contents of the Article 73 paragraph 2 of Law Number 30 Year 2014 on Government AdministrationKeywords : Implementation, Execution Of Documents, Notary